PEMAKNAAN SOSOK ANIES BASWEDAN DI COVER MAJALAH TEMPO TERKAIT WACANA CALON PRESIDEN 2024 - Sidiq, Muhammad; Adrianda, Irsan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The cover of magazines plays a crucial role in conveying messages and influencing public opinion, particularly through cartoon illustrations. This research focuses on Tempo magazine, known as one of Indonesia's critical media outlets, especially during the New Order regime. With the upcoming 2024 presidential election, Anies Baswedan has emerged as a presidential candidate supported by the Coalition for Change. The study titled